الثقافة الوافدة و علاقتها بمواقع التواصل الاجتماعي - بوزيد, سنية (كلية العلوم الإجتماعية لجامعة مستغانم, 2024)
تعتبر هذه الدراسة محاولة علمية لإيجاد التوافق والتفاعل بين الثقافة الوافدة ومواقع التواصل الاجتماعي عند الطلبة الجامعيين، والذين يعتبرون أهم فئة فعالة ونشطة في المجتمع باعتباره بذرة المستقبل، وتهدف الدراسة إلى معرفة العلاقة المتواجدة بين الثقافات الوافدة ووسائل التواصل الاجتماعي عند الشباب الجامعي وكذا تسليط الضوء على الجانب الاستهلاكي عند الطالب الجامعي للثقافة الخارجية. لقد تمت هذه الدراسة على عينة متمثلة في طلبة قسم علم الاجتماع بكلية العلوم الاجتماعية والانسانية، جامعة عبد الحميد ابن باديس -مستغانم-، واستعملنا المنهج الوصفي مع تقنية الاستمارة، وكذا الملاحظة بالمشاركة مع أفراد عينة البحث، وكذلك التدرب على إنجاز بحوث ميدانية من أجل التمكن من معالجة المشكلات المختلفة والقابلة للدراسة وكيفية استعمال الإجراءات المنهجية بطريقة علمية كل هذا أدى بنا إلى طرح تساؤل رئيسي وهو: مامدى تأثير الثقافات الوافدة على الشباب الجامعي في ظل ولوجها مع مواقع التواصل الاجتماعي؟
دراسة ميدانية على عينة من طلبة جامعة عبد الحميد بن باديس مستغانم
This study is considered a scientific attempt to find compatibility and interaction between foreign culture and social media among university students, who are considered the most important effective and active group in society as the seed of the future. The study aims to know the relationship that exists between foreign cultures and social media among university youth, as well as to shed light on the consumer side of foreign culture among university students. This study was conducted on a sample of students from the Department of Sociology at the Faculty of Social and Human Sciences, Abdelhamid Ibn Badis University - Mostaganem. We used the descriptive approach with the questionnaire technique, as well as observation by participating with members of the research sample, as well as training in conducting field research in order to Being able to address various problems that can be studied and how to use methodological procedures in a scientific manner All of this led us to ask a main question: To what extent is the influence of foreign cultures on university youth in light of their access to social networking sites?
Keywords: الثقافة، الثقافة الوافدة، مواقع التواصل الاجتماعي.; culture, expatriate culture, social networking sites.